A comparative study of subsoil profiles in southern end of golf ground, USM Kubang Kerian, Kelantan by density gradient tube technique - Rahim, Siti hasmah Ab (Universiti Sains Malaysia, 2006)
Soil is a common form of physical evidence found at the crime scene. It is a complex mixture with a variety of minerals. Considering the complexity of soil, various methods have been proposed for soil analysis. As with other physical evidence, forensic soil analysis is a comparative in nature. In my research, a density gradient tube technique is used to study and compare the sub soil profile. The purpose of this study is mainly to observe and study the differences in soil density. Samples have been collected in different points with different depths. The importance of the study is to determine the origin of the soil. For this study, soil samples were collected from four different points at a difference of 1 00' each with four different depths viz. top soil, soil at Y2 foot depth, 1 foot depth and 1 Y2 feet depth at southern end of Golf ground, USM Kubang Kerian, Kelantan. Altogether 16-soil samples have been collected for the study. The first step of analysis is the preliminary examination of soil viz. colour, general appearance, water content, pH and presence of any visible foreign materials. The next step is the microscopic examination of soil texture and presence of any other foreign materials. Then the particle sizes are measured by ocular micrometer. The fmal stage of analysis is density gradient tube technique to study distribution of soil particles. Soil sample preparation involves drying the soil under sun light and in hot air oven at a temperature of I 00°C for 3 hours. Then agitate the samples by using 125-J.I. sieve. The density gradient column was prepared by mixing bromoform and bromobenzene in different proportions, which contributes 6ml per layer and thus created 7 layers with 2 layers containing bromoform and bromobenzene only. These 7 layers have different densities. The bottom layer is high density bromoform and the top layer is low density bromobenzene. When soil sample is added to the gradient tube containing 7 layers, the soil particles sink in different layers corresponding to their density and the soil particles distribution can be observed. Comparison of soil samples were done in two stages. The first stage involved comparison of soil samples from different depth in the same point. The second stage involved comparison of soil samples from different points in the similar depths. All the results obtained were observed and recorded.